Hypoxia induced downregulation of hepcidin is mediated by platelet derived growth factor BB. Issue 12 (5th March 2014) - Sonnweber, Thomas; Nachbaur, David; Schroll, Andrea; Nairz, Manfred; Seifert, Markus; Demetz, Egon; Haschka, David; Mitterstiller, Anna-Maria; Kleinsasser, Axel; Burtscher, Martin; Trübsbach, Susanne; Murphy, Anthony T; et al.
Abstract : Objective: Hypoxia affects body iron homeostasis; however, the underlying mechanisms are incompletely understood. Design: Using a standardised hypoxia chamber, 23 healthy volunteers were subjected to hypoxic conditions, equivalent to an altitude of 5600 m, for 6 h. Subsequent experiments were performed in C57BL/6 mice, CREB-H knockout mice, primary hepatocytes and HepG2 cells. Results: Exposure of subjects to hypoxia resulted in a significant decrease of serum levels of the master regulator of iron homeostasis hepcidin and elevated concentrations of platelet derived growth factor (PDGF)-BB. Using correlation analysis, we identified PDGF-BB to be associated with hypoxia mediated hepcidin repression in humans. We then exposed mice to hypoxia using a standardised chamber and observed downregulation of hepatic hepcidin mRNA expression that was paralleled by elevated serum PDGF-BB protein concentrations and higher serum iron levels as compared with mice housed under normoxic conditions. PDGF-BB treatment in vitro and in vivo resulted in suppression of both steady state and BMP6 inducible hepcidin expression. Mechanistically, PDGF-BB inhibits hepcidin transcription by downregulating the protein expression of the transcription factors CREB and CREB-H, and pharmacological blockade or genetic ablation of these pathways abrogated the effects of PDGF-BB toward hepcidin expression. Conclusions: Hypoxia decreases hepatic hepcidin expression by a novel regulatory pathway exerted via PDGF-BB, leading to increased availability of circulating iron that can be used for erythropoiesis.